Kinerja Crossdraft Gasifier Dengan Bahan Bakar Tongkol Jagung Dengan Kecepatan Udara 3.0, 4.0, 5.0 m/s - SUMANTRI, KIKI; , NUR AKLIS,ST,M.Eng (2016)
Fossil fuels are the fuel that is not renewable (non-renewable). Total consumption of fossil fuels either petroleum, natural gas, or coal in Indonesia increasingly growing year. Corncob biomass is renewable energy and potential in Indonesia. Through gasification, burned corncobs with limited oxygen to produce syngas which is susceptible to burn. This study aims to determine the effect of air speed variation with temperature combustion, the temperature of boiling water, effective flame and thermal efficiency of the furnace. In this study begins by modifying the airways in the reactor, then the supply of air from the blower to vary the speed, size 170 mm diameter reactor. Air speed used was 3.0 m/s, 4.0 m/s and 5.0 m/s, then measured the combustion temperature and the temperature of boiling water every 1.0 minutes. The results showed variations in airspeed affects the combustion temperature, the temperature of boiling water, effective flame and furnace thermal efficiency generated. Air velocity 3.0 m/s for 611.67 C highest combustion temperature, the temperature of boiling water for 4.0 minutes, effective flame for 13 minutes.C highest combustion temperature, the temperature of boiling water for 8 minutes, effective flame for 16 minutes. Air velocity 5.0 m/s for 931.83C highest combustion temperature, the temperature of boiling water for 13 minutes, effective flame for 20 minutes. Air velocity 4.0 m/s for 815.67